2021
DOI: 10.1186/s12903-021-01927-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of health-promoting school strategy on dental plaque control and preventive behaviors in schoolchildren in high-caries, rural areas of Taiwan: a quasi-experimental design

Abstract: Background We evaluated the effects of health-promoting school (HPS) strategy on plaque control and behavior change in high-caries schoolchildren in Taitung, Taiwan. Methods A quasi-experimental design was adopted; six intervention schools (intervention group [IG]) and six comparison schools (comparison group [CG]) were selected from elementary schools with higher-than-average caries rates (> 68%). The IG was selected using cluster sampling, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The results of previous studies showed that the oral health practice scores of an intervention group who received oral health education increased, in line with our results (Bonabi et al, 2019;Haque et al, 2016). In this study, the participants showed an increase in tooth-brushing time and in tendency of self-efficiency toward thorough toothbrushing cleanly after the intervention at T1 compared to T0, and similar results were observed by Haque et al (2016) and Wei et al (2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of previous studies showed that the oral health practice scores of an intervention group who received oral health education increased, in line with our results (Bonabi et al, 2019;Haque et al, 2016). In this study, the participants showed an increase in tooth-brushing time and in tendency of self-efficiency toward thorough toothbrushing cleanly after the intervention at T1 compared to T0, and similar results were observed by Haque et al (2016) and Wei et al (2021).…”
Section: Discussionsupporting
confidence: 91%
“…To date, several reports have used a questionnaire regarding oral health practice and self‐efficacy in oral hygiene to evaluate the efficacy of oral health education (Bonabi et al, 2019 ; Haque et al, 2016 ; Kumar et al, 2022 ; Wei et al, 2021 ). The results of previous studies showed that the oral health practice scores of an intervention group who received oral health education increased, in line with our results (Bonabi et al, 2019 ; Haque et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resultados similares fueron observados en estudios previos, como el realizado por Borges-Yáñez, Castrejón-Pérez e Irigoyen (2017) en escolares de 6 a 13 años, donde un programa de cepillado dental supervisado mejoró las condiciones de higiene oral y redujo la placa dental, lo que respalda la importancia de la supervisión activa en el cuidado oral de los niños. Del mismo modo, Wei et al (2021) evaluaron una estrategia escolar de promoción de la salud que logró reducir la placa dental, mejorar el conocimiento sobre salud oral y aumentar la autoeficacia en higiene oral en escolares.…”
Section: Riosunclassified
“…In areas where children are suffering from various conditions, converging multiple interventions onto a single platform allows for maximizing efficiency, the scale of impact and sustainability. 15 The HPS framework has been employed to implement oral health interventions in several countries such as Taiwan, 16 the United Kingdom, 17 and Canada. 18 In Malaysia, the school health program under the Ministry of Health is a comprehensive and systematic program carried out in government schools.…”
Section: Introductionmentioning
confidence: 99%